BEBERAPA KARAKTERISTIK KIMIA TANAH PADA BERBAGAI KELERENGAN DAS POBOYA, KOTA PALU - Tambunan, Roosliana; Rajamuddin, Ulfiyah A.; Thaha, Abdul Rahim (AGROTEKBIS, 2018)
The research aims were to determine some chemical characteristics of soil under different position in slope land and to determine soil chemical characteristics under several toposequencein Poboya watershed of Palu.Â  Descriptive explorative method was employed to analyze data collected and the research variables were approached through field survey and supported by results of soil analysis in the Environment Laboratory of Faculty of Agriculture, Tadulako University.Â  The research was conducted in June â Desember 2015.Â  The differences of soil sites in slope position affected the soil chemical characteristics.Â  Soil pH was acid ranging from 4.55-5.78in the upper slope but slightly acid ranging from 4.65-6.28in the lower slope. Similarly, C-organic, N-total, C/N ratio, P-total, K-total and CEChad a tendency to be higher in the lower slope than in the upper slope.Â  Saturated bases were higher in the upper slope than in the lower slope.Â  Saturated basesalso tended to increase with soil depth at the upper slope.Â  In contrast, P-total and K-total tended to decrease with soil depth in the lower slope.Â Keywords: Poboya watershed, and Slope.